Expert Opinion on Current Trends in the Use of Insulin in the Management of People with Type 2 Diabetes from the South-Eastern European Region and Israel - Tabak, Adam G; Kempler, Peter; Guja, Cristian; Eldor, Roy; Haluzik, Martin; Klupa, Tomasz; Papanas, Nikolaos; Stoian, Anca Pantea; Mankovsky, Boris (Diabetes therapy, 2024)
Despite the availability of various antihyperglycaemic therapies and comprehensive guidelines, glycaemic control in diabetes management has not improved significantly during the last decade in the real-world clinical setting. Treatment inertia arising from a complex interplay among patient-, clinician- and healthcare-system-related factors is the prime reason for this suboptimal glycaemic control. Also, the key factor leading to inadequate glycaemic levels remains limited communication between healthcare professionals (HCPs) and people with type 2 diabetes (PwT2D). Early insulin administration has several advantages including reduced glucotoxicity, high efficacy and preserved β-cell mass/function, leading to lowering the risk of diabetes complications. The current publication is based on consensus of experts from the South-Eastern European region and Israel who reviewed the existing evidence and guidelines for the treatment of PwT2D. Herein, the experts emphasised the timely use of insulin, preferably second-generation basal insulin (BI) analogues and intensification using basal-plus therapy, as the most-potent glucose-lowering treatment choice in the real-world clinical setting. Despite an increase in the use of glucagon-like peptide-1 receptor agonists (GLP-1 RAs), the experts urged timely insulin initiation for inadequate glycaemic control in PwT2D. Furthermore, the combination of BI and GLP-1 RA addressing both fasting plasma glucose and post-prandial excursions as a free- or fixed-ratio combination was identified to reduce treatment complexity and burden. To minimise discontinuation and improve adherence, the experts reiterated quality, regular interactions and discussions between HCPs and PwT2D/carers for their involvement in the diabetes management decision-making process. Clinicians and HCPs should consider the opinions of the experts in accordance with the most recent recommendations for diabetes management.
Keywords: Intensification; Insulin initiation; Titration; Clinical practice; Israel; Type 2 diabetes; South-Eastern European region